Type designation for Reseda hookeri (Resedaceae) - Ferrer-Gallego, Pedro Pablo; Ferrando, Inmaculada; Laguna, Emilio (Phytotaxa, 2015)
The typification of the name Reseda hookeri Guss. (Resedaceae) is discussed. The designation of the corresponding type is based on the consultation of Gussone’s original material and the literature cited in the protologue. A specimen at NAP (Herbarium Neapolitanum, University of Naples, Italy) is designated as the lectotype, and a specimen at BOLO (Herbarium of the University of Bologna, Italy) is designated as the epitype.